Struktur Komunitas dan Status Konservasi Ikan Berdasarkan Alat Tangkap Tradisional di Desa Simonis Kabupaten Labuhan Batu Utara - Ritonga, Irna Alfaini; Khairul, Khairul; Harahap, Hasmi Syahputra (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Fish diversity must be maintained because it has an ecological role, namely maintaining the balance of the ecosystem and can be used as an indicator of pollution. diversity is also important for the balance of aquatic ecosystems and some simonis villagers make it a community livelihood.Â  Based on information from residents of Simonis Village, North Labuhan Batu Regency, it is recognized that the diversity found in the river is quite high. In addition, residents of simonis village, north labuhan batu district can also utilize river water in pulo biski as drinking water, washing clothes, bathing and tourism.Â  This study aims to determine the community structure, ecological index and conservation status of fish obtained in Simonis Village based on IUCN data. This research is a survey with the determination of observation stations through purposive sampling method. Fish sampling was carried out using environmentally friendly fishing gear such as nets, shoots, fishing rods and tanggok or nets. The results of this study obtained approximately 22 species of fish and each fish species and morphological identification was carried out in order to know the scientific name of each type of fish. Index value and Diversity with moderate category. Diversity Index value with high category. Dominance Index value with no dominance criteria. It is concluded that the diversity of fish in Simonis Village, North Port Batu Regency.